Microplastic-Mediated Transfer of Tetracycline Resistance: Unveiling the Role of Mussels in Marine Ecosystems - Giovanni Milani; Claudia Cortimiglia; Mireya Viviana Belloso Daza; Emanuele Greco; Daniela Bassi; Pier Sandro Cocconcelli (MDPI AG, 2024)
The global threat of antimicrobial resistance (AMR) is exacerbated by the mobilization of antimicrobial resistance genes (ARGs) occurring in different environmental niches, including seawater. Marine environments serve as reservoirs for resistant bacteria and ARGs, further complicated by the ubiquity of microplastics (MPs). MPs can adsorb pollutants and promote bacterial biofilm formation, creating conditions favorable to the dissemination of ARGs. This study explores the dynamics of ARG transfer in the marine bivalve Mytilus galloprovincialis within a seawater model, focusing on the influence of polyethylene MPs on the mobilization of the Tn916-carrying tetM gene and plasmid-encoded ermB. Experiments revealed that biofilm formation on MPs by Enterococcus faecium and Listeria monocytogenes facilitated the transfer of the tetM resistance gene, but not the ermB gene. Furthermore, the presence of MPs significantly increased the conjugation frequency of tetM within mussels, indicating that MPs enhance the potential for ARG mobilization in marine environments. These findings highlight the role of MPs and marine organisms in ARG spread, underscoring the ecological and public health implications.